Biological control of the spittlebugs (Aeneolamia spp. and Prosapia spp.) with use Metarhizium anisopliae in Brachiaria decumbens grasslands in El Petén, Guatemala - Castillo Zeno, Salvador (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2014)
Tesis (Mag. Sc) -- CATIE, Turrialba (Costa Rica),2006